Understanding the Role of Alcohol, Anxiety, and Trait Mindfulness in the Perpetration of Physical and Sexual Dating Violence in Emerging Adults. (August 2018) - Ngo, Quyen M.; Ramirez, Jessica I.; Stein, Sara F.; Cunningham, Rebecca M.; Chermack, Stephen T.; Singh, Vijay; Walton, Maureen A.
This study examines alcohol consumption, anxiety, trait mindfulness, and physical and sexual dating violence aggression (PDV and SDV) among 735 emerging adults (18-25 years) in an urban emergency department. Of the total sample, 27.2% perpetrated PDV and 16.5% perpetrated SDV. Alcohol was positively associated with PDV/SDV. Anxiety was positively associated with PDV. Mindfulness was negatively associated with PDV/SDV. Interaction analyses revealed women had lower PDV with higher nonjudgment facet of mindfulness. Higher act aware was associated with lower PDV regardless of high versus low alcohol. Findings indicate different contributing factors among perpetrators of PDV/SDV; some factors may be attenuated by mindfulness.